Transformation Research and the Longue Durée of 1989: Combining Qualitative and Quantitative Data - Brückweh, Kerstin; Zöller, Kathrin (Przegląd Socjologii Jakościowej, 2019)
In recent years, historians have increasingly looked at social science data in their search for sources to study the transformation period. Researchers hope that a secondary analysis of this data will expand the existing sources. This expansion promises new perspectives, while simultaneously bringing new methodological challenges to the discipline. This article deals with both: 1. It uses a history of knowledge approach to evaluate the topics and tools of transformation research. It also argues that social scientists were not only producers of knowledge but historical actors in the restructuring of the institutions of social sciences in East Germany after 1989/90. 2. With the German Socio-Economic Panel and especially the Saxonian Longitudinal Study as an example, the article refers to the content of the studies itself – in this case, the East German school as a site of life-worlds in upheaval. It concludes that the encounter of social scientists and historians is very fruitful for historians interested in the interaction of system change and everyday life. That is, the secondary analysis of qualitative and quantitative social science data compliments ‘classical’ sources of historical research by providing insights into memories and experiences at different times in the historical process.